Description of immatures of Chelymorpha reimoseri Spaeth, 1928 (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini) - Świętojańska, Jolanta; Massuda, Kamila Ferreira; Stach, Małgorzata; Borowiec, Lech (Zootaxa, 2015)
Immature stages of Chelymorpha reimoseri Spaeth, 1928 are described in detail, including line drawings, chaetotaxy, sculpture of integument, and SEM photos of morphological details. It is the first detailed description of immatures in the genus Chelymorpha Chevrolat, 1836 and the fourth in the tribe Mesomphaliini Chapuis, 1875 which include chaetotaxy of the body. Diagnostic characters for this species in comparison with other described larvae and pupae of the genus Chelymorpha are discussed. Some remarks on the biology of Ch. reimoseri, are also given.